CHARACTERIZATION OF BUILT HERITAGES IN A SECOND ORDER CITY IN ANDHRA PRADESH, INDIA - Giduthuri, Viswanadha Kumar (European Scientific Journal, ESJ, 2015)
In continuation of the pursuit related to the human endeavor of heritages in second order cities in India, a comprehensive study on heritage resources present in Vizianagaram town, Andhra Pradesh, India was taken up next to the earlier attempt at Visakhapatnam city. Vizianagaram town forming a part of the Visakhapatnam Metropolitan Region was found to harbour 24 important heritage structures and sites representing reasonable number of architectural styles and typologies and the same are analyzed and discussed in this communication. In the light of re-formulation of Andhra Pradesh state and ambitions to develop mega and smart cities with capital at Vijayawada, the present study assumes greater significance to providing information for the synthesis of the noted heritages with urban landscape to promote historical, cultural and socio-economic merits of the town.